2022
DOI: 10.1002/smll.202206125
|View full text |Cite
|
Sign up to set email alerts
|

Gradient‐Structured Ceramics with High Energy Storage Performance and Excellent Stability

Abstract: Owing to the high power density, eco‐friendly, and outstanding stability, the lead‐free ceramics have attracted great interest in the fields of pulsed power systems. Nevertheless, the low energy storage density of such ceramics is undoubtedly a severe problem in practical applications. To overcome this limitation, the lead‐free ceramics with gradient structures are designed and fabricated using the tape‐casting method herein. By optimizing the composition and distribution of the gradient‐structured ceramics, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…Very recently, giant W rec > 15 J cm –3 has been advanced in a few NaNbO 3 (NN)-based , and Bi 0.5 Na 0.5 TiO 3 (BNT)-based ceramics, while their corresponding η is relatively low (∼80%), owing to the open hysteresis loops at high field. High η (>90%) can be obtained in some BaTiO 3 (BT)-based, SrTiO 3 (ST)-based ceramics, but their W rec is typically below 8 J cm –3 , limited by the relatively low intrinsic polarization. Furthermore, various mesoscopic-structural modulation strategies have been proposed to enhance E B . ,,, However, owing to the inherent trade-off between P m , H , and E B in dielectrics, achieving “dual high” performance, for example, going beyond the current boundary of W rec > 15 J cm –3 and η > 90% in bulk ceramics, remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, giant W rec > 15 J cm –3 has been advanced in a few NaNbO 3 (NN)-based , and Bi 0.5 Na 0.5 TiO 3 (BNT)-based ceramics, while their corresponding η is relatively low (∼80%), owing to the open hysteresis loops at high field. High η (>90%) can be obtained in some BaTiO 3 (BT)-based, SrTiO 3 (ST)-based ceramics, but their W rec is typically below 8 J cm –3 , limited by the relatively low intrinsic polarization. Furthermore, various mesoscopic-structural modulation strategies have been proposed to enhance E B . ,,, However, owing to the inherent trade-off between P m , H , and E B in dielectrics, achieving “dual high” performance, for example, going beyond the current boundary of W rec > 15 J cm –3 and η > 90% in bulk ceramics, remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the energy storage density of Ba 2 Bi 4 Ti 5 O 18 ceramic is lower compared to that of some other perovskite (ABO 3 )-based ceramics. [46][47][48] The literature have shown that the spontaneous polarization is mainly determined by three components: the movement of the B-site ions, the degree of tilt of the oxygen octahedron along the c-axis, and the rotation of the oxygen octahedron in the a-b plane. [16,49,50] Since the spontaneous polarization of bismuth-layered compounds is limited by their crystal structure and can only rotate in the a and b planes in two dimensions, the energy storage density of Ba nÀ3 Bi 4 Ti n O 3nþ3 (n = 4-7) ceramics prepared by the conventional solid-state method is relatively low.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed description of these terms can be seen in the previous literature. [ 46 ] Ba 2 Bi 4 Ti 5 O 18 ceramic owns the best energy storage performance with high W rec ≈ 1.16 J cm −3 and η ≈ 87.2% (under 250 kV cm −1 ). The difference in crystal structure leads to a different spontaneous polarization mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Dielectric capacitors have attracted considerable attention in the electronics industry and electrical power systems, due to their extraordinary charge-discharge rate and ultra-high power density. [1][2][3][4][5] Polymerbased dielectric materials are considered as their key component for superior flexibility, low weight, facile processing, inexpensive production, and high tolerance of voltage. [6][7][8] However, the energy storage performances of pure polymerbased capacitors usually deteriorate rapidly with temperature rising, because of the intrinsic property of thermal-activated charge transport, which are unable to meet the urgent need for dielectric capacitors with high energy-density and hightemperature capability under critical operating environments.…”
Section: Introductionmentioning
confidence: 99%